Liability for animals a comparative study: south African and German law - Muller, Stephanie (School For Advanced Legal Studies, 2023)
The field of' Liability for Animals' appears at first sight to be only of minor interest to academics. This, however, is a false syllogism as incidents involving animals are frequent, and courts constantly deal with claims regarding damages for injuries caused by animals. Indeed, in many countries the law of animals forms special subject. With respect to English law for instance Lord Simonds, using the metaphor of a train, remarked that the Common Law of torts has developed historically in separate compartments and that beasts have travelled in a compartment of their own. 1 However, it is also true, that within this "tort-train" a few animals lurking in the other compartments marked 'Negligence or Nuisance' may also be found.